1990
DOI: 10.1161/01.cir.82.4.1476
|View full text |Cite
|
Sign up to set email alerts
|

Hirudin, heparin, and placebo during deep arterial injury in the pig. The in vivo role of thrombin in platelet-mediated thrombosis.

Abstract: Three dosages (0.3, 0.7, and 1.0 mg/kg) of recombinant hirudin, a specific inhibitor of thrombin, were compared with heparin (50 units/kg) and placebo for reducing thrombus formation in the carotid arteries of 50 pigs after deep injury by balloon dilatation. Each drug was administered as a bolus followed immediately by a continuous infusion of the same dose per hour. Major end points were quantitative indium-111-labeled platelet and iodine-125-labeled fibrinogen deposition and the incidence of mural thrombosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
71
1
2

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(79 citation statements)
references
References 25 publications
(5 reference statements)
5
71
1
2
Order By: Relevance
“…Growth of thrombus induced by preformed, fresh mural thrombus was lowest in pigs treated with the specific thrombin inhibitor r-hirudin at a dose that prevented macroscopic mural thrombus after deep injury 13,14 and increased with decreasing antithrombin activity, confirming our previous results. 9 Thrombus size in animals treated with aspirin was not significantly reduced at these rheological conditions, a finding that is consistent with previous results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Growth of thrombus induced by preformed, fresh mural thrombus was lowest in pigs treated with the specific thrombin inhibitor r-hirudin at a dose that prevented macroscopic mural thrombus after deep injury 13,14 and increased with decreasing antithrombin activity, confirming our previous results. 9 Thrombus size in animals treated with aspirin was not significantly reduced at these rheological conditions, a finding that is consistent with previous results.…”
Section: Discussionsupporting
confidence: 89%
“…9,22 Thrombin plays a central role in the formation, growth, maintenance, and consolidation of thrombus. Direct thrombin inhibition with hirudin, but not heparin, blocks these processes and leads to profound inhibition of thrombus 14,[23][24][25] and even to dissolution of preformed thrombus, as in our study. In vivo, in the pig with a carotid artery crush injury, 90% of the preformed, half-hour-old thrombus dissolved within 1 hour of hirudin administration.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The effect of these commonly used drugs on platelet deposition is well known. 21 Our model confirmed the weak antiplatelet effects of aspirin, 22 the modest effect of heparin, and the potent effect of hirudin but, importantly, showed that compared with flow measurements, monitoring continuous isotope-labeled platelet deposition can more sensitively quantify thrombus formation, even before changes in flow or total occlusion occur.…”
Section: Discussionsupporting
confidence: 66%
“…When higher doses (aPTT Ͼ2 times control) were used, acute mural thrombosis was totally abolished and platelet-vessel wall interaction was reduced to a monolayer. 9,10 Further evidence supporting the hypothesis of thrombin as a major mediator of restenosis comes from studies using hirudin 13 and recombinant tick anticoagulant peptide (rTAP) in the cholesterol-fed rabbit femoral artery model. 30 TAP, by binding and inhibiting factor Xa, also inhibits thrombin generation at the initiation of the coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%